Penyalahgunaan Bentuk Badan Hukum Yayasan dalam Program Makan Bergizi Gratis: Analisis Hukum Dagang terhadap Kemitraan SPPG - Deril Rafsya Timora; Irsyad Ayatullah; Ardiansyah Ardiansyah; Yuda Saputra; Muhammad Alwan Nazhif; Muhammad Hilmi; Muhammad Irfan Hakim; Nandang Najmudin (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
The Free Nutritious Meals Program (MBG), launched by President Prabowo Subianto's administration in January 2025, operates a food distribution mechanism through Nutrition Service Units (SPPG), which are largely managed by foundations (yayasan). This study examines the misuse of the foundation legal entity form in the context of SPPG partnerships from a commercial law perspective by analyzing the discrepancy between the non-profit character of foundations and the commercial activities carried out in practice. This research applies a normative juridical method with statutory and conceptual approaches. The findings indicate that several SPPG partner foundations operate beyond the authority permitted by Law No. 16 of 2001 as amended by Law No. 28 of 2004 on Foundations, conduct covert commercial activities, and potentially violate the ultra vires prohibition. An Indonesia Corruption Watch (ICW) investigation in 2025 found that 89 of 102 examined MBG partner foundations (87.25%) were affiliated with political parties or state officials. This condition creates conflicts of interest that are inconsistent with the principles of sound commercial law. This article recommends regulatory reform of SPPG partnerships, the application of the piercing the corporate veil doctrine to foundations that abuse their legal entity status, and strengthened oversight mechanisms by the National Nutrition Agency (BGN).